Notes on resin collected by stingless bees in Taman Tropika Tasik Kenyir, Terengganu, Malaysia - Mohd. Fahimee Jaapar,; Nur Syazwani Nasarodin,; Nurul Farisa Reward,; Rosliza Jajuli,; Idris Abd. Ghani, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
A study to investigate the resin collection behaviour of stingless bees was conducted on three different species of Dipterocarpaceae trees, namely Keruing (Dipterocarpus grandiflorus), Damar hitam (Shorea balanocarpoides) and Meranti (Shorea parvifolia) between January to March 2018. Three digital single-lens reflexes DSLR with macro lens attached was used to record resin collection of stingless bees in front of three trees for 5 min per hour between 0900 to 1600 h for a day per 3 months. Result showed that there was a significant difference in the mean numbers of resin-foraging stingless bees (F=9.91; df=7, 23; P˂0.05) on Keruing between 0900 h to 1600 h for three months samplings. Similar result was observed on Meranti (F=7.21; df=7, 23; P˂0.05) and Damar hitam (F=21.37; d=7, 23; P˂0.05) in the mean number of resin collecting by stingless bees right between 0900 h to 1600 h. The highest number of resin collected by stingless bees was at 1300 hours followed by 1200 hours. A total of 2,730 individual embracing 11 species of stingless bees were recorded collecting resin headed by Homotrigona fimbriata followed by Tetragonilla collina and Tetrigona apicalis. Thus, it is hope these data would be a guideline for farmers to enhance their meliponiculture.